Innovation and Internationalisation in Higher Education : рroсeedings of the British-Ukrainian Conference (London, 16 October 2025) = Інновації та інтернаціоналізація у вищій освіті : матеріали британсько-української конференції (Лондон, 16 жовтня 2025 р.) - (:unkn) unknown (Одеса : Юридична література, 2025)
The proceedings of the British-Ukrainian Conference “Innovation and Internationalisation in Higher Education” are devoted to the development of joint educational and research initiatives, strengthening academic mobility, and promoting the exchange of experience between the academic communities of both countries. They also highlight the creation of new formats of cooperation in the fields of research, technology, and innovation. The implementation of British educational practices and international standards serves as a key factor in reforming the higher education system of Ukraine, contributing to its modernisation and successful integration into the European and global educational and research space. Матеріали британсько-української конференції «Інновації та інтернаціоналізація у вищій освіті» присвячені розвитку спільних освітніх і наукових ініціатив, посиленню академічної мобільності, обміну досвідом між науково-педагогічними спільнотами двох країн, а також створенню нових форматів взаємодії у сфері досліджень, технологій та інновацій. Застосування британських освітніх практик і міжнародних стандартів є важливим чинником реформування системи вищої освіти України, сприяючи її модернізації та успішній інтеграції в європейський та міжнародний освітній і науковий простір.
Innovation and Internationalisation in Higher Education : рroсeedings of the British-Ukrainian Conference (London, 16 October 2025) = Інновації та інтернаціоналізація у вищій освіті : матеріали британсько-української конференції (Лондон, 16 жовт. 2025 р.) / edited by S. V. Kivalov ; executive editor D. A. Minchenko ; International Education Corporation ; National University “Odesa Law Academy”. – Odesa : Yurydychna Literatura, 2025. – 520 p. - Режим доступу: https://doi.org/10.32837/11300.31737
Keywords: інтернаціоналізація у вищій освіті; обмін досвідом між країнами; британські освітні практики; Internationalisation in Higher Education